Structural and Semantic Similarity Measurement of UML Use Case Diagram - Arifin, Mohammad Nazir; Siahaan, Daniel (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 11 No 2 (2020): Vol. 11, No. 2 August 2020DO - 10.24843/LKJITI.2020.v11.i02.p03, 2020)
Reusing software has several benefits ranging from reducing cost and risk, accelerating development, and its primary purposes are improving software quality. In the early stage of software development, reusing existing software artifacts may increase the benefit of reusing software because it uses mature artifacts from previous artifacts. One of software artifacts is diagram, and in order to assist the reusing diagram is to find the level of similarity of diagrams. This paper proposes a method for measuring the similarity of the use case diagram using structural and semantic aspects. For structural similarity measurement, Graph Edit Distance is used by transforming each factor and use case into a graph, while for semantic similarity measurement, WordNet, WuPalmer, and Levenshtein were used. The experimentation was conducted on ten datasets from various projects. The results of the method were compared with the results of assessments from experts. The measurement of agreement between experts and method was done by using Gwet’s AC1 and Pearson correlation coefficient. Measurement results with Gwet’s AC1 diagram similarity are 0,60, which were categorized as “moderate" agreement and the result of measurement with Pearson is 0.506 which means there is a significant correlation between experts and methods. The result showed that the proposed method can be used to find the similarity of the diagram, so finding and reuse of the diagram as a software component can be optimized.